ANALISIS KINERJA RASIO PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - Shafira Azzahra; Sifa Nuraeni; Ruli Mochammad Chaerudin; Tatiek Ekawati Permana; Yunyun Ratna (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2024)
This study aims to see how the best profitability performance among the five pharmaceutical sector manufacturing companies, namely PT Sido Muncul, PT Kimia Farma, PT Kalbe Farma, PT Indofarma and PT Pyridam Farma as the object under study from secondary data in the form of financial reports available on the Indonesia Stock Exchange during the 2019-2022 period. This is reflected in the average value of the GPM, NPM, and ROA ratios which are higher than their competitors. The method used is descriptive quantitative. The results show that PT Sido Muncul has the best profitability performance among the five companies, characterized by a higher average value of profitability ratios, on the other hand PT Kimia Farma shows the lowest performance, and the case of PT Indofarma attracts attention because although it has a very high Return on Equity (ROE), this is more due to the use of significant debt than the company's operational efficiency.